Development of Molding Compounds Based on Epoxy Resin/Aromatic Amine/Benzoxazine for High‐Temperature Electronic Packaging Applications. Issue 12 (9th July 2022) - Gou, Haolan; Bao, Ying; Huang, Jiateng; Fei, Xiaoma; Li, Xiaojie; Wei, Wei
Abstract: Heat‐resistant molding of compounds is an indispensable part in encapsulating future electronic power devices. Herein, it is used for polyfunctional epoxy resin (EP) and diamine‐phenol benzoxazine (BOZ) as resin matrix, 4, 4'‐diaminodiphenylmethane (DDM) as curing agent, and iron acetylacetonate (Fe(acac)3 ) as curing accelerator, as well as inorganic fillers and other auxiliaries, to prepare heat‐resistant molding compounds. The curing behavior, processability and thermal performance of the EP/DDM/BOZ (EDB) resin blends containing different contents of DDM, BOZ, and Fe(acac)3 are first systematically investigated. The EDB molding compounds (MCEDB ) with suitable BOZ content show good processability, and the molding process can be compatible with that of commercial epoxy molding compounds (EMC). With increasing the BOZ content, the glass transition temperature of cured MCEDB is greatly enhanced to a maximum of 261 °C determined by dynamic mechanical analyzer, owing to the hydrogen‐bond interaction generated after polymerization of BOZ increasing the rigidity of network chains. Moreover, the cured MCEDB also exhibits higher thermal decomposition stability, better high‐temperature (200 °C) mechanical properties, and lower water absorption compared to the cured EMC. After high‐temperature (200 °C) aging for 500 h, the cured MCEDB with suitable BOZ content still maintains outstanding performance. This study provides a promising strategy for preparing heat‐resistant electronic packaging molding compounds. Abstract : In this work, heat‐resistant molding compounds based on epoxy resin/aromatic amine/benzoxazine are successfully developed. The cured molding compounds exhibit excellent thermal decomposition stability, high‐temperature (200 °C) mechanical properties, and lower water absorption, as well as superior high‐temperature aging resistance, compared to the typical epoxy molding compounds. This work provides a promising candidate as heat‐resistant materials for encapsulating future high‐power devices.